The Impact of the Issue of Demarcation on Pre-service Teachers' Beliefs on the Nature of Science - (:unkn) unknown (EDAM, 2010)
The arguments about the dimensions of nature of science and the strategies for teaching it are still controversial. In this research, as part of these arguments, a context based on the issue of demarcation of science from pseudoscience was offered and questioned for its effectiveness in nature of science teaching. The research was planned for an educational term and astrology was examined as a case in this context for the criteria proposed by philosophers. A questionnaire composed of open-ended questions which was analyzed qualitatively and used as data source. The results of the research indicated that the context designed was effective in developing the nature of science understandings in various dimensions such as science as an enterprise, experiments, observations, theories, laws, models, scientific methods and the role of socio-cultural values in science.
Keywords: The Issue of Demarcation; Nature of Science; STUDENTS VIEWS; CONCEPTIONS; EXPLICIT; INSTRUCTION; IMPLICIT; CONTEXT; 6TH